Integrating Biofeedback in Dynamic Biomechanical Gait Training for Chronic Ankle Instability - Byong Hun Kim; Tae Kyu Kang; Sae Yong Lee (Applied Sciences)
Gait analysis was performed in patients with chronic ankle instability (CAI). Despite advancements in rehabilitation techniques, the integration of gait-training strategies with concurrent feedback (visual and auditory) remains underexplored. This study aimed to investigate the dynamic biomechanical characteristics of CAI patients using a gait-training device following a 6-week intervention program. Thirty patients with CAI (Intervention Group; Sex: Male 8, Female 7, Age: 30.6 ± 4.08, Height: 170.49 ± 11.09 cm), (Control Group; Sex: Male 9, Female 6, Age: 30.49 ± 4.39, Height: 171.63 ± 9.90 cm) participated in this single-blind, randomized controlled trial. The intervention group completed six weeks of gait training using novel devices. Following the intervention, dorsiflexion angles increased significantly from 88.66 ± 5.47% to 92.60 ± 4.45% (p = 0.002) for the FAAM-ADL score, while FAAM-Sport scores improved from 80.79 ± 8.20% to 85.67 ± 6.41% (p = 0.000). Increased dorsiflexion and eversion angles were observed during the early to mid-late stance and late swing phases of gait for both walking and running. Joint moments demonstrated significant changes, with dorsiflexion, eversion, and abduction tendencies increasing throughout the gait cycle after the intervention. The newly developed inertial measurement unit (IMU) proved to be a viable gait-training device for CAI, highlighting that concurrent feedback may allow for greater improvements in deficiencies associated with CAI.